ECOLOGY OE LIMNOFAUNA IN THE SMALL STREAMS AND THEIR IMPORTANCE TO THE VILLAGE LIFE IN GARHWAL HIMALAYA - DOBRIYAL, ANOOP K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
The present paper describes the general ecology of limnofauna in the small streams of Garhwal Himalaya and their importance to the village people. Special attention have been paid to the potamobiology of the small stream 'Chakagadera," a tributary of the river Mandakini.